Ratings of perceived exertion-lactate association during actual singles tennis match play - Mendez-Villanueva, A.; Fernandez-Fernandez, J.; Bishop, D.; Fernandez-Garcia, B. (The Journal of Strength and Conditioning Research, 2010)
To examine the relationship between metabolic (i.e., blood lactate concentration) and perceptual (ratings of perceived exertion, RPE) responses and their association with variables describing the characteristics of the singles tennis match play. Eight trained and internationally ranked (Association of Tennis Professionals rankings) male tennis players were studied during singles matches (best of 3 sets) played on an outdoor clay court surface during a professional invitational tournament. Ratings of perceived exertion and blood lactate concentrations were determined at selected changeovers during the game. The variables describing the characteristics of the matches, (a) duration of rallies (DR), (b) rest time, (c) effective playing time, and (d) strokes per rally (SR), were determined from video recordings. Significant correlations (r = 0.57-0.48; p < 0.01) were found for RPE-blood lactate responses during the games. Both RPE and blood lactate concentration values were significantly correlated with SR and DR (r = 0.80-0.61; p < 0.001) in service games. Average RPE was significantly higher (p < 0.05) following service games (13.5 +/- 1.9; n = 24) than following receiving games (12.2 +/- 2.0; n = 22). Mean blood lactate concentrations were significantly higher (p < 0.05) following service games (4.4 +/- 2.4 mmol[middle dot]L-1; n = 24) than following receiving games (3.0 +/- 1.3 mmol[middle dot]L-1; n = 22). These results indicate that monitoring RPE may be a useful technique for regulating on-court tennis training intensity. Moreover, blood lactate may mediate the relation between RPE and tennis match play intensity.